The discovery of significant oil and gas fields in the United States - Nehring, Richard; Van Driest, E. Reginald, 1945-; Rand eBooks (Santa Monica, CA : RAND, 1981)
A quantitative assessment of the ultimate conventional petroleum resources of the United States. Using a database listing all the significant oil and gas fields, the authors describe what has already been discovered, interpret why these discoveries happened when they did, and assess the remaining geologic prospects. U.S. petroleum resources are highly concentrated in a few major provinces and in a relatively small number of giant and large fields. Since the peaks in oil discoveries about 1930 and natural gas about 1950, both the number of discoveries and the amounts discovered have declined substantially. The authors conclude that most of the conventional petroleum that will ultimately be produced has already been discovered and made recoverable. Ultimate recovery will most likely be between 210 and 285 billion barrels of petroleum liquids and 920 to 1,090 trillion cubic feet of natural gas, as compared with known recovery of 175 billion barrels and 750 trillion cubic feet.
"January 1981."
Includes errata and addenda.
Includes bibliographical references (p. 179-236).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Gas fields -- United States; Oil fields -- United States; Electronic books